2020
DOI: 10.1515/tnsci-2020-0099
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet-induced obesity and impairment of brain neurotransmitter pool

Abstract: AbstractObesity and the brain are linked since the brain can control the weight of the body through its neurotransmitters. The aim of the present study was to investigate the effect of high-fat diet (HFD)-induced obesity on brain functioning through the measurement of brain glutamate, dopamine, and serotonin metabolic pools. In the present study, two groups of rats served as subjects. Group 1 was fed a normal diet and named as the lean group. Group 2 was fed an HFD for 4 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 61 publications
(65 reference statements)
1
23
0
Order By: Relevance
“…The results indicated that the 5-HT levels of college students played a partial mediating role between over-weight/obesity and EC. First, overweight/obesity probably result in lower 5-HT levels [ 26 ] and, thus diminished the core subcortical/cortical region activity such as amygdala and medial prefrontal cortex, and reduce the activity of the underlying neural networks, which might impair the performance of EC [ 62 , 63 , 64 ]. Second, high 5-HT levels can exert direct effects on their receptors within the prefrontal cortex and hippocampus, and improve performance of EC at least in part via those mechanisms [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the 5-HT levels of college students played a partial mediating role between over-weight/obesity and EC. First, overweight/obesity probably result in lower 5-HT levels [ 26 ] and, thus diminished the core subcortical/cortical region activity such as amygdala and medial prefrontal cortex, and reduce the activity of the underlying neural networks, which might impair the performance of EC [ 62 , 63 , 64 ]. Second, high 5-HT levels can exert direct effects on their receptors within the prefrontal cortex and hippocampus, and improve performance of EC at least in part via those mechanisms [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was additionally found that overweight/obesity can reduce 5-HT production. The disruption of the energy balance due to excess caloric intake and reduced energy consumption cause onset of metabolic disorders, leading to decreased 5-HT levels [ 22 , 23 , 24 , 25 , 26 ]. At the same time, many scholars use functional magnetic resonance imaging (fMRI) technology to show the acute influence that the drug regulating the 5-HT system has on brain activation in the process of individual participation in EC.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is probably one of the reasons responsible for the high weight gained by the group fed margarine and canola. There is close relationship between the percentage of fat in canola and margarine but no relationship existed between the percentage of fat in canola and the control and the percentage of fat in margarine and control [9].…”
Section: Sample Codementioning
confidence: 85%
“…Dopamine (DA) is well known to mediate immune responses in the periphery through its receptors expressed in immune cells (Arreola et al, 2016 ). High levels of brain DA and altered amounts of other neurotransmitters have been detected in obese animals compared to those in the lean group along with an increase in inflammatory mediators and oxidative markers (Labban et al, 2020 ). TFP has been reported to inhibit cytokine release from LPS-stimulated macrophages and dendritic cells and acts as a potential anti-sepsis drug (Park et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%